BIM handbook : a guide to building information modeling for owners, managers, designers, engineers, and contractors - Eastman, Charles M. (Hoboken, N.J. : Wiley, 2008)
"The BIM Handbook is an extensively researched and meticulously written book, showing evidence of years of work rather than something that has been quickly put together in the course of a few months. It brings together most of the current information about BIM, its history, as well as its potential future in one convenient place, and can serve as a handy reference book on BIM for anyone who is involved in the design, construction, and operation of buildings and needs to know about the technologies that support it. The need for such a book is indisputable, and it is terrific that Chuck Eastman and his team were able to step up to the plate and make it happen. Thanks to their efforts, anyone in the AEC industry looking for a deeper understanding of BIM now knows exactly where to look for it."
Chapter 1 BIM Handbook Introduction -- Chapter 2 BIM Design Tools and Parametric Modeling -- Chapter 3 Interoperability -- Chapter 4 BIM for Owners and Facility Managers -- Chapter 5 BIM for Architects and Engineers -- Chapter 6 BIM for the Construction Industry -- Chapter 7 BIM for Subcontractors and Fabricators -- Chapter 8 The Future: Building with BIM -- Chapter 9 BIM Case Studies.
Includes bibliographical references (p. 469-480) and index.
1
Keywords: Building -- Computer simulation -- Handbooks, manuals, etc; Building management -- Data processing -- Handbooks, manuals, etc; Communication in the building trades -- Handbooks, manuals, etc; Architectural practice -- Handbooks, manuals, etc; Architects and builders -- Handbooks, manuals, etc; Construction industry -- Information resources management -- Handbooks, manuals, etc